2022
DOI: 10.3389/fimmu.2021.797390
|View full text |Cite
|
Sign up to set email alerts
|

The PDE4 Inhibitor Tanimilast Blunts Proinflammatory Dendritic Cell Activation by SARS-CoV-2 ssRNAs

Abstract: Phosphodiesterase 4 (PDE4) inhibitors are immunomodulatory drugs approved to treat diseases associated with chronic inflammatory conditions, such as COPD, psoriasis and atopic dermatitis. Tanimilast (international non-proprietary name of CHF6001) is a novel, potent and selective inhaled PDE4 inhibitor in advanced clinical development for the treatment of COPD. To begin testing its potential in limiting hyperinflammation and immune dysregulation associated to SARS-CoV-2 infection, we took advantage of an in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 66 publications
2
15
0
Order By: Relevance
“…Going forward, it has been revealed that Th1-attracting CXCL10 or CXCL9 concentrations were reduced by Tanimilast. Knowing that CXCL10, on which this review focuses on, is one of the most important factors that amplify the immune response through the requirement of Th1 cells, thus, it was suggested that PDE4 inhibitors are a promising therapeutic option for COVID-19 [ 66 ]. Similar to the above-described drugs, Pelargonium sidoides DC .…”
Section: Resultsmentioning
confidence: 99%
“…Going forward, it has been revealed that Th1-attracting CXCL10 or CXCL9 concentrations were reduced by Tanimilast. Knowing that CXCL10, on which this review focuses on, is one of the most important factors that amplify the immune response through the requirement of Th1 cells, thus, it was suggested that PDE4 inhibitors are a promising therapeutic option for COVID-19 [ 66 ]. Similar to the above-described drugs, Pelargonium sidoides DC .…”
Section: Resultsmentioning
confidence: 99%
“…Tanimilast displays prominent anti-inflammatory properties in several cell-based models [ 7 , 36 ] as well as in experimental rodent models of pulmonary inflammation [ 17 ] and in clinical settings [ 6 ]. In addition, we have previously demonstrated that it also finely tunes, rather than suppressing, the cytokine network produced by inflamed DCs, thus potentially modulating T cell polarization and adaptive effector functions [ 18 , 37 ]. Here, we characterized TAN-LPS-moDCs as compared to BUD-LPS-moDCs as activators of CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The GSEA enrichment analysis showed that gene sets grouped according to IGSF6 expression were mainly enriched in cytokine-receptor interaction and intercellular interaction. It has been well established that the antigen peptide-MHCII complex presented by macrophages and DCs is essential for the activation of Th1 cells [28][29][30][31]. Previous studies have also proposed that IGSF6 may be closely related to antigen uptake or the recirculation of DCs [13].…”
Section: Discussionmentioning
confidence: 99%